2015
DOI: 10.1590/1414-431x20154467
|View full text |Cite
|
Sign up to set email alerts
|

Caryocar brasiliense camb protects against genomic and oxidative damage in urethane-induced lung carcinogenesis

Abstract: The antioxidant effects of Caryocar brasiliense Camb, commonly known as the pequi fruit, have not been evaluated to determine their protective effects against oxidative damage in lung carcinogenesis. In the present study, we evaluated the role of pequi fruit against urethane-induced DNA damage and oxidative stress in forty 8-12 week old male BALB/C mice. An in vivo comet assay was performed to assess DNA damage in lung tissues and changes in lipid peroxidation and redox cycle antioxidants were monitored for ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 39 publications
1
25
0
3
Order By: Relevance
“…However, this fruit has been poorly studied. To the author's knowledge, there are only some research showing healing (Quirino et al, 2009;Bezerra et al, 2015), chemopreventive (Palmeira et al, 2016;Colombo et al, 2015) and anti-inflammatory (MirandaVilela et al, 2009) properties of pequi oil. Studies regarding functional properties from pequi pulp intake are scarce (Teixeira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, this fruit has been poorly studied. To the author's knowledge, there are only some research showing healing (Quirino et al, 2009;Bezerra et al, 2015), chemopreventive (Palmeira et al, 2016;Colombo et al, 2015) and anti-inflammatory (MirandaVilela et al, 2009) properties of pequi oil. Studies regarding functional properties from pequi pulp intake are scarce (Teixeira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, C. brasiliense pulp oil and an ethanolic extract of the pulp affected urethaneinduced lung cancer in BALB/C mice and restored urethane-mediated conformational changes of deoxyribonucleic acid (DNA), suggesting that pequi may modify the carcinogenic process either by blocking the development of early lesions or by inhibiting the progression to invasive cancer (Colombo et al, 2015). Khouri et al (2007) and Miranda-Vilela et al (2008) suggested that C. brasiliense pulp, as chloroform or aqueous extract, has anticlastogenic and antimutagenic potentials, being able to inhibit cyclophosphamide (CP)-and bleomycin (BLM)-induced DNA damage in mice.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…When combined, these compounds can act as preventive agents in cancer, scavenging free radicals, improving the antioxidant defense system, and increasing the activities and expression of antioxidant enzymes at the protein and genomic level, thus reducing oxidative stress and its consequences. Therefore, further investigations are required to elucidate the role of each active constituent of pequi to determine the molecular mechanisms involved and to develop targeted therapies for cancer treatment (Colombo et al, 2015;Miranda-Vilela et al, 2014;Almeida et al, 2012;Miranda-Vilela et al, 2011;Khouri et al, 2007).…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Pequi pulp is rich in lipids, dietary fiber, carotenoids and phenolic compounds (CORDEIRO et al, 2013;RIBEIRO et al, 2014). According to in vivo studies, the consumption of pequi pulp oil can improve the antioxidant defense system (COLOMBO et al, 2015) and shows hypolipidemic effects, decreasing oxidative stress and inflammatory processes (FIGUEIREDO et al, 2016).…”
Section: Introductionmentioning
confidence: 99%